OPEN INNOVATION AND KNOWLEDGE MANAGEMENT - Celadon, Kleber Luís (Seven Editora, 2025)
The use of external and internal ideas to advance knowledge is pointed out as a factor that provides greater competitiveness for companies in general. The flow of knowledge in and out, an integral part of this process, involves practices that should encourage participants to explore a wide range of innovation opportunities through multiple channels (WEST; GALLAGHER, 2006).Several authors point out that innovation processes can no longer be restricted to local or in-house know-how, and should prioritize professionals capable of maximizing their effectiveness, as well as seeking alternative sources, such as markets or knowledge spillovers (ACHA, 2006; CELADON, 2007; CHESBROUGH, 2003b; COHEN; LEVINTHAL, 1990; EASTERBY-SMITH; PRIETO, 2008; HOWELLS, 1996; NONAKA; TAKEUCHI, 1995; POLANYI, 1958). An example of this in the cosmetics sector is the search for specialized and unique knowledge - such as that of experienced perfumers - which is often available in other countries. In addition, emerging markets can be exploited according to changes in socio-economic circumstances.This dynamic requires interaction and integration of knowledge, which is related to the concept of Knowledge Integration, defined as an organizational learning process and considered critical to the competitiveness of companies.Both Open Innovation and Knowledge Integration show complementarities, but also overlapping dimensions - aspects that have not yet been compared in previous studies. These concepts may even prove to be antagonistic, requiring research to explore this relationship. It should also be considered that strategic formulation can influence organizational forms and practices (PENROSE, 1959), as well as the critical dimensions of innovation, such as offers, market presence, customers and processes (SAWHNEY; WOLCOTT; ARRONIZ, 2006). This analysis is particularly relevant in low and medium technology industries, which are still little studied.The current economic context encourages companies to adopt Open Innovation and Knowledge Integration mechanisms in order to achieve success. Thus, this research aims to investigate how companies articulate these concepts in practice. The Brazilian economy is still largely sustained by low and medium-low technology companies, which makes the study of these organizations - and not just high-tech companies - essential for the country's future economic development.A comparative analysis was carried out on a specific sector, the cosmetics, toiletries and perfumery sector - hereafter referred to simply as the cosmetics sector/industry in this work.DOI: https://doi.org/10.56238/sevened2025.026-007